Effects of the technique of cryopreservation and dilution/centrifugation after thawing on the motility and vitality of spermatozoa of oligoasthenozoospermic men - Esteves Sandro C.; Spaine Deborah M.; Cedenho Agnaldo P.; Srougi Miguel (International Brazilian Journal of Urology, 2003)
OBJECTIVE: Comparing in human semen samples with low initial quality, the effects of 2 techniques of cryopreservation and dilution/centrifugation after thawing on the spermatic motility and vitality. MATERIALS AND METHODS: Semen samples from 15 oligo and/or asthenozoospermic individuals assisted in the infertility sector of a tertiary hospital were obtained through masturbation. The samples were divided into 2 portions of equal volume, and diluted (1:1; v/v) with the cryoprotector containing glycerol (Test yolk buffer). One portion was frozen through the technique of liquid nitrogen vapor with static phases (group I - GI), while the other was frozen through a programmable biological freezer with linear speed (Planer, Kryo 10, series III) (group II - GII). The following parameters were assessed before freezing and after thawing: percentage of spermatozoa with progressive motility (Prog%) and percentage of live spermatozoa (Vit%). After defrosting, Prog% was assessed before and after removal of cryoprotector diluent, in different time intervals (zero, 3 h, and 24 h). The statistical analysis has been accomplished by using the non-parametric tests of Wilcoxon and Friedman. RESULTS: There was significant reduction of Prog% and Vit% from before freezing to after defrosting in both groups, I and II (p < 0.001). Values of Prog% and Vit% were not statistically different between groups, after thawing. It has been observed a significant reduction in Prog% among portions frozen with the automated technique after dilution and centrifugation for removal of cryoprotector (p = 0.006). After cryoprotector removal, Prog% has been kept unaltered, in both groups, during the first 3 hours of incubation, although being superior in group I (p = 0,04). There was a significant decrease in Prog% after 24 hours of incubation, in both groups (p < 0,01). CONCLUSION: For human semen samples with low initial quality, freezing through vapor technique or through the automated technique showed to be equivalent in regarding recovery of live spermatozoa with progressive motility. The effects of dilution and centrifugation to remove the cryoprotector had a negative impact only in samples frozen through the automated technique. In both techniques, progressive motility is kept constant during the first 3 hours after thawing and removal of the cryoprotector, but is drastically diminished by the end of an incubation period of 24 hours.